Botulinum toxin in bruxism treatment - Piotr Piech; Hanna Sudzińska; Justyna Pietrak; Maciej Kozioł; Monika Maślanko; Karolina Wilczyńska; Jadwiga Kozioł; Robert Łuczyk (Kazimierz Wielki University, 2017)
Introduction: Bruxism is defined as abnormal, fixed, unconscious chewing organ function, deviating qualitatively and quantitatively from normal function. Another definition speaks of motor dysfunction in the mouth, characterized by grinding and clenching of the teeth, occurring during sleep. The etiology of this disorder has not been explained until now, but it is believed to be related to localized, mental, nervous and neurotransmitter disorders. Purpose: The aim of the study is to review literature and knowledge about the use of botulinum toxin in the treatment of bruxism. Methods of treatment: The patient reports to the physician usually after a distressing, difficult to locate pain. The basis for proper treatment is to detect parafunctions and to make the patient aware of their existence. Diagnostic symptoms include dentinal lesions, recesses, enamel cracks and abfractive cavities, as well as changes in the mucosal area of the cheeks. Treatment begins with the use of an occlusive therapy to relax muscles, reduce parafunction and relieve pain. In the form of severe pain, NSAIDs are introduced and, if necessary, anxiolytics, sedatives and antidepressants. In the absence of response to the treatment used, botulinum toxin type A injections are used. The dose of the agent depends on the initial muscle tone and the effect of decrease in its activity is maintained for 4 to 6 months. Conclusions: The use of botulinum toxin makes it possible to selectively exclude overactive muscles, which is a great advantage over other techniques. An additional benefit of this therapy is achieved good cosmetic effect, reversible effect and minimal amount of side effects.